Blood pressure control and antihypertensive pharmacotherapy patterns in a hypertensive population of Eastern Central Region of Portugal - Morgado, Manuel (2010)
BACKGROUND: Interventions to improve blood pressure control in hypertension have had limited success in clinical practice despite evidence of cardiovascular disease prevention in randomised controlled trials. The objectives of this study were to evaluate blood pressure control and antihypertensive pharmacotherapy patterns in a population of Eastern Central Region of Portugal, attending a hospital outpatient clinic (ambulatory setting) for routine follow-up. METHODS: Medical data of all patients that attended at least two medical appointments of hypertension / dyslipidemia in a university hospital over a one and a half year period (from January 2008 to June 2009) were retrospectively analysed. Demographic variables, clinical data and blood pressure values of hypertensive patients included in the study, as well as prescribing metrics were examined on a descriptive basis and expressed as the mean +/- SD, frequency and percentages. Student's test and Mann-Whitney rank sum test were used to compare continuous variables and chi-square test and Fisher exact probability test were used to test for differences between categorical variables. RESULTS: In all, 37% of hypertensive patients (n=76) had their blood pressure controlled according to international guidelines. About 45.5% of patients with a target blood pressure <140/90 mmHg (n=156) were controlled, whereas in patients with diabetes or chronic kidney disease (n=49) the corresponding figure was only 10.2% (P<0.001). Among patients initiating hypertension / dyslipidemia consultation within the study period 32.1% had stage 2 hypertension in the first appointment, but this figure decreased to 3.6% in the last consultation (P=0.012). Thiazide-type diuretics were the most prescribed antihypertensive drugs (67%) followed by angiotensin receptor blockers (60%) and beta-blockers (43%). About 95.9% patients with comorbid diabetes were treated with an angiotensin-converting enzyme inhibitor or an angiotensin receptor blocker. CONCLUSIONS: Clinically important blood pressure decreases can be achieved soon after hypertension medical appointment initiation. However, many hypertensive patients prescribed with antihypertensive therapy fail to achieve blood pressure control in clinical practice, this control being worse among patients with diabetes or chronic kidney disease. As pharmacotherapy patterns seem to coincide with international guidelines, further research is needed to identify the causes of poor blood pressure control.